Additives for Environmentally Adapted Lubricants - Tribo Film Formation - Anders Pettersson (Japanese Society of Tribologists, 2008)
Five different anti-wear additives, suitable to formulate environmentally adapted hydraulic fluids, were tested. The used base fluid was a saturated, environmentally adapted synthetic complex ester. The tested materials were steel-steel and bronze-steel. A modified Falex pin and a vee-block tester were used for the tribotests. XPS was used to characterize the surfaces. It was found that the new types of more polar additives work better than the traditional ones, though they can give selective transfer of cupper to the steel pin. To use this type of additives in fully formulated products more investigations have to be performed.